Anthropic risks generated by mining activity - Argüello Mejía, Ana Violeta (2013)
Productive activities generate anthropic risks in the medium and long term. The study area is located in the parishes of Pomasqui, San Antonio and Calacalí, where risks have occurred due to human activities. In this case, because of the exploitation of the quarries to supply the construction market of the Metropolitan District of Quito. This research aims to determine the anthropic risks generated by mining activities. The inhabitants of the area identified that artisanal mining, at the beginning, was a source of work where their families were also involved. Currently, it is observed that most of the quarries use specialized machines and inhabitants do not work there. The quarries slopes are 80° and 90° that create hazards for workers and residents of nearby houses. One of the biggest impacts is air pollution; however, soil and water courses are affected by mining waste. The population, which is permanently exposed to the dust caused by quarrying and transport of material, accuses respiratory diseases. Also, the noise caused by transport is a constant annoyance for residents.